ҚАЗАҚ ЖӘНЕ ЖАПОН ТІЛДЕРІНДЕГІ ЕЛІКТЕУІШ СӨЗДЕР - Нурелова,, А. М.; Рустемова, А. М. (Journal of Oriental Studies, 2016)
В статье рассматривается особенности звукоподра-жательных слов казахском и японском языках. А такжестепень изученности, как часть речи, морфологическаяструктура, виды ономатопе.This article examined the similarities and differencesmimetic words in Japanese and Kazakh languages. It alsocovers issues of research mimetic words in two languages,as part of speech, morphological